Infinity, faith and time : Christian humanism and Renaissance literature - Hill, John Spencer, 1943- (McGill-Queen's studies in the history of religion., 1997)
"Infinity, Faith, and Time is an exploration of Renaissance literature and the importance of a powerful tradition of Christian-Platonist rational spirituality derived from St Augustine and Nicholas of Cusa. John Spencer Hill argues that this tradition had a formative role in the thought of Renaissance writers by enabling them to assimilate into their worldview two central discoveries of the Renaissance - that the universe is possibly infinite and that human existence is bound and regulated by the passage of time."--Jacket